PERTUMBUHAN DAN PRODUKTIVITAS JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA TUMBUH LIMBAH BLOTONG DAN AMPAS TEBU DENGAN TAMBAHAN BEKATUL - Purwaningsih, Ch. Endang (Widya Warta, 2014)
This research was intended to investigate the growth and productivity of oyster mushroom planted on mixed media of filtered cake sugarcane and baggase added with rice bran. Thisexperiment applied Completely Randomized Design (CRD) with three replicates. There were five levels of threatment, namely P0+B: control; P1+B:20% filtered cake sugarcane + 80%baggase; P2+B: 30% filtered cake sugarcane + 70% baggase; P3+B: 40% filtered cake sugarcane + 60% baggase ;and P4+B: 50% filtered cake sugarcane + 50% baggase. All ofthe threatments were done with the addition of rice bran. The parameters measured were miselium length increasement, fruit body number, total fresh weight, total dry weight, stalklength, and pileus width. The collected data were analyzed using Analysis of Variance (Anova), followed by Least Significant Difference (LSD) test at 5% level of significance. Theresult of this experiment showed that oyster mushroom (Pleurotus ostreatus) grew well on mixed media of filtered cake sugarcane and baggase added with rice bran. Growth mediumon P2+B threatment gave oyster mushroom (Pleurotus ostreatus) best productivity in fruit body number (55,67 pieces), total fresh weight (252,28 g), and total dry weight (27,77 g).